PENGARUH CITRA MEREK DAN KUALITAS PRODUK TERHADAP KEPUTUSAN KONSUMEN MEMBELI PRODUK MOBIL TOYOTA AVANZA PADA PT. AGUNG AUTOMALL CABANG JAMBI - Ahmad Tarmizi (Universitas Batanghari Jambi, 2014)
In this study using survey method, survey method is a method of research that takes a sample from a population and a questionnaire as data collection tools and information that is relevant to the problem dieliti. The purpose of this study is as follows: To analyze the effect of brand image, product quality, and consumer decision to buy a Toyota Avanza at. Agung Automall Branch Jambi. To maganalisispengaruh brand image and product quality affect consumer decisions membelimobil Toyota Avanza at. Agung Automall Branch Jambi. In this study using survey method, survey method is a method of research that takes a sample from a population and a questionnaire as data collection tools and information that is relevant to the problem under study.Based on the results of multiple linear regression brand image (X1) of 0.047 states that each additional 1% of the value of X1 will increase consumer purchasing decisions (Y) of 04.7%. Based on the test results obtained partial degrees of freedom (df) = 97, α of 0.05 with the criterion for the consumer's decision to buy is: 0.680 t <t table 1.985, so the statement the second hypothesis H0 is accepted and H1 is rejected, which means the partial image of the brand does not affect the consumer's decision to buy. Based on the analysis of determination obtained results koefisiendeterminasi R2 value (R Square) 0.69, in other words the image of the brand (X1) and product quality (X2) jointly influence the consumer's decision to buy (Y) is equal to 69.1%, while the remaining 30.9% were caused by other factors beyond the variables studied. And based upon a simultaneous test (F test) results obtained f values calculated 105.984 at the significance level of 5% (0.000 <0.05) was obtained 3.09 f table. Value of F 105.984> f table 3.09, then H0 is rejected and H1 is accepted so that it can be said that seluruhvariabel brand image and product quality jointly influence the consumer decision to buy the product at PT Toyota Avanza. Agung Automall Jambi branch.Keywords: Image, Quality, Consumer